Fecal and Serum Metabolomic Signatures and Microbial Community Profiling of Postmenopausal Osteoporosis Mice Model - Wen, Kaicheng; Tao, Lin; Tao, Zhengbo; Meng, Yan; Zhou, Siming; Chen, Jianhua; Yang, Keda; Da, Wacili; Zhu, Yue (Frontiers in Cellular and Infection Microbiology, 2020)
Multiple studies have shown that an imbalance in the intestinal microbiota is related to bone metabolism, but the role of the intestinal microbiota in postmenopausal osteoporosis remains to be elucidated. We explored the effect of the intestinal microbiota on osteoporosis. We constructed a postmenopausal osteoporosis mouse model, and Micro CT was used to observe changes in bone structure. Then, we identified the abundance of intestinal microbiota by 16S RNA sequencing and found that the ratio of Firmicutes and Bacteroidetes increased significantly. UHPLC-MS analysis was further used to analyse changes in metabolites in faeces and serum. We identified 53 upregulated and 61 downregulated metabolites in faeces and 2 upregulated and 22 downregulated metabolites in serum under OP conditions, and interestedly, one group of bile acids showed significant differences in the OP and control groups. Network analysis also found that these bile acids had a strong relationship with the same family, Eggerthellaceae. Random forest analysis confirmed the effectiveness of the serum and faecal models in distinguishing the OP group from the control group. These results indicated that changes in the gut microbiota and metabolites in faeces and serum were responsible for the occurrence and development of postmenopausal osteoporosis. The gut microbiota is a vital inducer of osteoporosis and could regulate the pathogenesis process through the “microbiota-gut-metabolite-bone” axis, and some components of this axis are potential biomarkers, providing a new entry point for the future study on the pathogenesis of postmenopausal osteoporosis.